ITEM ANALYSIS OF LISTENING TEST FOR NINTH-GRADE STUDENTS - Icha Anggreaini Pratama; Sastri, Lena; Irwandi; Amiza, Elsi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is conducted due to several problems in the English listening test used by the teacher. The English teacher did not consider the difficulty level of the test items, did not analyze whether the items could distinguish students’ abilities, did not conduct item analysis, and used a test with an unbalanced distribution of difficulty levels. Therefore, this research aimed to analyze the difficulty level and discrimination index of English listening test items used at SMP N 1 Bukittinggi. This research used a descriptive quantitative method. The data were obtained from students’ scores on an English listening test consisting of 10 true/false items. The data were analyzed using formulas proposed by Brown & Abeywickrama. The results showed that the listening test items were valid but not reliable, with a reliability coefficient of 0.40. Based on the difficulty level analysis, 6 items (60%) were categorized as easy and 4 items (40%) as moderate. No difficult items were found, indicating that the test was relatively easy for the students. The discrimination index analysis showed that 5 items (50%) were classified as good, 4 items (40%) as satisfactory, and 1 item (10%) as poor. Overall, the listening test did not meet the criteria of a good quality test.